A GIS Framework to Identify The Suitability Map to Utilize Sand Deposited Land in Dibru River Basin: Using AHP Method and MCDM - Sonowal, Gulap; Thakuriah, Gitika; Saikia, Palash Moni (Geological Agency, 2026)
The site suitability for utilizing sand deposited land is an important step towards sustainable development by adopting conservative measures. Soil is the most crucial for maintaining an environment and ecosystem which is helpful to sustaining all forms of life. The increasing action of sand deposition day to day has been one of the common issues all over the world, especially the country with high magnitude flood. The present study aim is to identify the sensitive area of the sand deposition within The Dibru River Basin. Multicriteria evaluation is carried out using Geographic Information System (GIS) techniques to help the choice makers in identifying the suitable site of sand deposition. Different layers which were considered for multicriteria evaluation are: sand deposition, geomorphology, soil capability, soil texture, and slope for identifying the vulnerable zone of sand deposition. Analytical Hierarchy Processes (AHP) are used for weighted sum to find the sensitive area of the sand deposition for land management using selected criteria. The site suitability map was classified into low, moderate, and high deposition zones. This paper will help policy makers for implementing the preventive measures to use the siltation zone into sustainable agriculture practise within The Dibru River Basin.